Theoretical Aspects of Managing the Innovative Development of Bioeconomic Branches - Nizamov Akmal Asliddinovich; Ravshanovna, Ravshanova Gulchehra (International Journal on Orange Technologies, 2023)
This study examines the theoretical aspects of managing the innovative development of bioeconomy industries. At the present stage, the innovative development of bioeconomy sectors is an important component in the transition from an economy with a raw material orientation to an economy of an innovative type. As prerequisites for the formation of a bioeconomy, one can note an increase in the use of renewable sources of raw materials, the introduction of new methods of deep processing and the biologization of the human environment.